2017
DOI: 10.1182/blood-2017-01-760702
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PIM kinases in Reed-Sternberg cells fosters immune privilege and tumor cell survival in Hodgkin lymphoma

Abstract: Reed-Sternberg (RS) cells of classical Hodgkin lymphoma (cHL) express multiple immunoregulatory proteins that shape the cHL microenvironment and allow tumor cells to evade immune surveillance. Expression of certain immunoregulatory proteins is modulated by prosurvival transcription factors, such as NFκB and STATs. Because these factors also induce expression of the oncogenic PIM1/2/3 serine/threonine kinases, and as PIMs modulate transcriptional activity of NFκB and STATs, we hypothesized that these kinases su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…A recent study on adoptive T-cell therapy (ACT) has suggested that PIM inhibition could be used alongside anti-PD1 (programmed death receptor 1) therapy. 139 The cells obtained from PIM knock-out mice had lower glycolytic activity, S6 phosphorylation, interferon gamma secretion, and ROS levels than those from wild-type mice, which translates to decreased T-cell death, an increased memory phenotype, and superior tumor control and mouse survival. A similar outcome was demonstrated following treatment with AZD1208.…”
Section: Pim and Immunotherapymentioning
confidence: 93%
See 1 more Smart Citation
“…A recent study on adoptive T-cell therapy (ACT) has suggested that PIM inhibition could be used alongside anti-PD1 (programmed death receptor 1) therapy. 139 The cells obtained from PIM knock-out mice had lower glycolytic activity, S6 phosphorylation, interferon gamma secretion, and ROS levels than those from wild-type mice, which translates to decreased T-cell death, an increased memory phenotype, and superior tumor control and mouse survival. A similar outcome was demonstrated following treatment with AZD1208.…”
Section: Pim and Immunotherapymentioning
confidence: 93%
“…Treatment with kaempferol led to lower body weight loss and higher survival than the control treatment. 138 In Hodgkin lymphoma, PIM kinases have been shown to contribute to the immunosuppressive environment through modulation of PD-L1/2 (programmed death-ligand) activity, and although the PIMs are not key drivers of this phenotype, there is some rationale to support investigating the co-targeting of the PIM family (via the pan-PIM inhibitor SEL24) with PDL-1 (139). A recent study on adoptive T-cell therapy (ACT) has suggested that PIM inhibition could be used alongside anti-PD1 (programmed death receptor 1) therapy.…”
Section: Pim and Immunotherapymentioning
confidence: 99%
“…Its protein is expressed in the thymus, liver, spleen, and hematopoietic progenitor cells in the bone marrow during development [13]. Expression of PIM1 has been noted in B-cell, T-cell, and Hodgkin lymphomas [1, 14-16] as well as in myeloid and lymphoid leukemias [13]. Based on our previous studies indicating that the PIM1 gene cooperates with the human BCL6 gene to promote the development of lymphomas [1] and the finding that both BCL6 and PIM1 are expressed in CLL/SLL [2], we hypothesized that quercetin, a PIM1 kinase inhibitor, might be a useful agent for targeted antitumor effects in CLL/SLL.…”
Section: Discussionmentioning
confidence: 99%
“…Among the common downstream targets of the JAK-STAT and NF-kB pathways are PIM serine/threonine kinases, which have been shown to be highly expressed in cHL cell lines and primary HRS cells. 87 Targeting of PIM kinases with a pan-PIM inhibitor resulted in tumor cell apoptosis, attenuated JAK-STAT and NF-kB signaling, and marked reduction of immunomodulatory molecules, such as galectin-1 and programmed death receptor ligands 1 and 2 (PD-L1/2), in the preclinical setting. 87 Besides JAK-STAT and NF-kB, multiple additional signaling cascades are deregulated and constitutively active in HRS cells, including the PI3K-AKT pathway.…”
Section: Interference With Pathway Dependenciesmentioning
confidence: 99%
“…87 Targeting of PIM kinases with a pan-PIM inhibitor resulted in tumor cell apoptosis, attenuated JAK-STAT and NF-kB signaling, and marked reduction of immunomodulatory molecules, such as galectin-1 and programmed death receptor ligands 1 and 2 (PD-L1/2), in the preclinical setting. 87 Besides JAK-STAT and NF-kB, multiple additional signaling cascades are deregulated and constitutively active in HRS cells, including the PI3K-AKT pathway. 88 HRS cells also show aberrant expression of multiple receptor tyrosine kinases, including platelet-derived growth factor receptor-a, epithelial discoidin domain-containing receptor 2, TRKA, and TRKB, 89 which are reported to result in downstream phosphorylation and activation of AKT1.…”
Section: Interference With Pathway Dependenciesmentioning
confidence: 99%